2022
DOI: 10.1155/2022/1714041
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-186-5p Downregulates NAMPT and Functions as a Potential Therapeutic Target for Sepsis-Induced Coagulation Disorders

Abstract: Purpose. Present study is aimed to explore the role of miR-186-5p in sepsis-induced coagulation disorders and molecular mechanisms. Methods. Thirty-four sepsis patients and 34 respiratory infection/pneumonia patients were selected in the present study. Polymicrobial sepsis model was created by cecal ligation and puncture (CLP). The mRNA expression was detected by qRT-PCR. Western blot was utilized to measure protein expression. Thromborel S Reagent was applied to measure the prothrombin time (PT). Platelet cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In addition, miR-186-5p has previously been reported as a circulating biomarker of cardiovascular risk, contributing to the diagnosis of acute coronary syndrome [37][38]. MiRNA-186-5p inhibits sepsis induced coagulation disorders by targeting NAMPT and inactivating the NF-κB pathway [39]. Recent studies have con rmed that the upregulation of PVT1 by hypoxia can promote the expression of CTGF, resulting in autophagy disactivation and abnormal proliferation of pulmonary artery smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-186-5p has previously been reported as a circulating biomarker of cardiovascular risk, contributing to the diagnosis of acute coronary syndrome [37][38]. MiRNA-186-5p inhibits sepsis induced coagulation disorders by targeting NAMPT and inactivating the NF-κB pathway [39]. Recent studies have con rmed that the upregulation of PVT1 by hypoxia can promote the expression of CTGF, resulting in autophagy disactivation and abnormal proliferation of pulmonary artery smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Computational Intelligence and Neuroscience has retracted the article titled “MiR-186-5p Downregulates NAMPT and Functions as a Potential Therapeutic Target for Sepsis-Induced Coagulation Disorders” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
“…Computational Intelligence and Neuroscience has retracted the article titled "MiR-186-5p Downregulates NAMPT and Functions as a Potential Terapeutic Target for Sepsis-Induced Coagulation Disorders" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%